2000
DOI: 10.1128/mcb.20.6.2043-2054.2000
|View full text |Cite
|
Sign up to set email alerts
|

Etk, a Btk Family Tyrosine Kinase, Mediates Cellular Transformation by Linking Src to STAT3 Activation

Abstract: Etk (also calledBmxEtk (also called Bmx) is a member of the Btk nonreceptor tyrosine kinase family (48,51,57). This family of kinases is characterized by a modular structure, including an N-terminal pleckstrin homology (PH) domain, a Tec homology domain, Src homology 2 (SH2) and SH3 domains, and a C-terminal kinase domain. Many members of the Btk family are predominantly expressed in cells of hematopoietic origin. Btk is expressed in B cells and myeloid cell lineages and is essential for B-cell development and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
117
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(125 citation statements)
references
References 69 publications
8
117
0
Order By: Relevance
“…These data together suggest that Tec family kinases are bidirectional switches of cell growth and apoptosis. While the mechanism of this switch is presently unclear, we noted that Etk assumes two forms inside the cells: the wild-type form which requires upstream signals such as PI-3 kinase, FAK, PTPD1, and Src for its activation (Ekman et al, 2000;Jui et al, 2000;Tsai et al, 2000;Chen et al, 2001), and the caspase-8 truncated form which is constitutively active. We previously showed that the constitutively activated form induced apoptosis (Wu et al, 2001).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…These data together suggest that Tec family kinases are bidirectional switches of cell growth and apoptosis. While the mechanism of this switch is presently unclear, we noted that Etk assumes two forms inside the cells: the wild-type form which requires upstream signals such as PI-3 kinase, FAK, PTPD1, and Src for its activation (Ekman et al, 2000;Jui et al, 2000;Tsai et al, 2000;Chen et al, 2001), and the caspase-8 truncated form which is constitutively active. We previously showed that the constitutively activated form induced apoptosis (Wu et al, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…There are a number of reports suggesting a role of Tec family kinases in growth and antiapoptosis. For example, Etk has been shown to be a critical mediator of cellular transformation through a cascade link of vSrc-Etk-Stat3 (Tsai et al, 2000) in fibroblast and epithelial cells. Overexpression of Etk stimulates the proliferation of MCF-7 breast cancer cells and protects prostate cancer cells from ionization-and thapsigargininduced apoptosis (Xue et al, 1999;Bagheri-Yarmand et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations